Transition of deletion mutants of the composite resistance plasmid NR1 in Escherichia coli and Salmonella typhimurium. - Huffman, G A (1984)
Derivatives of the composite R plasmid NR1 from which a portion of the resistance determinants (r-determinants) component had been deleted were found to undergo amplification of the remaining r-determinants region in Escherichia coli and Salmonella typhimurium. The wild-type NR1 plasmid does not amplify in these genera, although all of these plasmids undergo amplification in Proteus mirabilis. The deletion mutants retained the mercuric ion resistance operon (mer) but conferred a much lower level of sulfonamide resistance than NR1. The remaining r-determinants region, which is bounded by direct repeats of the insertion element IS1, formed multiple tandem duplications in E. coli, S. typhimurium, and P. mirabilis after subculturing the host cells in medium containing high concentrations of sulfonamide. Gene amplification was characterized by restriction endonuclease analysis, analytical buoyant density centrifugation, DNA-DNA hybridization, and sedimentation in sucrose gradients. The tandem repeats remained attached to the resistance transfer factor component of the plasmid in at least part of the plasmid population; autonomous tandem repeats of r-determinants were probably also present. Amplification did not occur in host recA mutants. Amplified strains subcultured in drug-free medium lost the amplified r-determinants. By using a strain temperature sensitive for the recA gene, it was possible to obtain gene amplification at the permissive temperature. Loss of r-determinants took place at the permissive temperature, but not at the nonpermissive temperature. The termini of the deletions of several independent mutants which conferred low sulfonamide resistance were found to be located within the adjacent streptomycin-spectinomycin resistance gene.